Strategi Rumah Sakit dalam Mengembangkan Kompetensi Layanan Sahabat Pelanggan untuk Mendukung Terwujudnya Pelayanan Prima di RSUD Kota Bogor - Patrick, Patrick; Prayogi, Ratnawati; Rismadi, Bambang; Rudianto, Rudianto (Jurnal Manajemen, 2025)
This research analyzes strategies for enhancing the competence of Customer Service personnel to improve the quality of healthcare services. Employing a qualitative approach, the research utilizes in-depth interviews, observations, and document analysis for data collection. The findings reveal that essential competencies for personnel include effective communication skills, empathy, and basic medical knowledge. Despite the implementation of the Customer Service concept, challenges such as insufficient ongoing training programs and poor coordination among units persist, hindering service quality. To address these issues, the study proposes strategies involving continuous training, the enhancement of information systems, and performance evaluations based on SERVQUAL indicators. Implementing these strategies is expected to significantly improve service quality at RSUD Kota Bogor, thereby enhancing the hospital's reputation as a provider of high-quality, family-friendly healthcare services. This research aims to assist hospital management in developing more effective policies for building the competencies of Customer Service personnel, ultimately contributing to improved patient satisfaction and loyalty.